(untitled) (London Journal of Research In Science: Natural and Formal, 2026)
The metallurgical industry in Rafaela faces significant challenges related to competitiveness and the integration of digital technologies into its production processes. This study addresses the problem of how small and medium-sized enterprises (SMEs) in the sector can improve their efficiency and adapt to a globalised market environment through digital transformation. To address this problem, an exploratory-descriptive self-diagnosis methodology was applied, using structured questionnaires to assess the levels of knowledge, integration, systematisation, and innovation in key areas such as design, procurement, manufacturing, administration, and sales. The results reveal an uneven adoption of digital technologies within these companies, with a notable reliance on manual systems in critical areas and low nformation integration between departments. The proposed solution is based on implementing a digital transformation framework that enables companies to improve their processes and foster a culture of technological advancement and continuous training. In conclusion, comprehensive digital transformation emerges as a necessary step for Rafaela’s metallurgical SMEs to enhance their competitiveness, efficiency, and adaptability in a dynamic market context. The adoption of advanced technologies and improved organisational integration are key factors for the success of this process and for ensuring sustainable long- term growth.